Pembinaan dan pengujian kebok optik pantulan penuh sinar-x - Munhamad Jaib, Manan; Yunus, Jasmy; Lee, Siak Kuan (Universiti Teknologi Malaysia, 2005)
Optical box for the TXRF system was developed. Alignment for the total reflection point of the x-ray beams has been done manually. Sampel targetted at the reflection point has been tested. Sampels with difference concentrations have been used. Linearity of the system was good. The detection power of the system is better for quarts compared to perspects.